Points of Resistance to Lectio Divina: An Anthropological Perspective. Issue 1 (April 2021) - D. G. Irvine, Richard
Abstract : What is distinctive about lectio divina as a practice? What does it require of us, and for what purpose? This ethnographic response considers the relational character of lectio divina and examines the social context of reading as listening. As a way of bringing its characteristics into relief, I describe two ways in which we might find ourselves resisting this slow, prayerful reading. Firstly, the resistance of the body, as it struggles with the physiological challenge of slowing down the pace and recasting reading as an auditory process. Secondly, the resistance of the self, uncomfortable with having to cede control. Lectio divina sits in awkward tension with a world dependent on speed and grounded in individualism.